Impact of Paternal Age at Conception on Human Health. (1st January 2019) - Simard, Mathieu; Laprise, Catherine; Girard, Simon L
Abstract: BACKGROUND: The effect of maternal age at conception on various aspects of offspring health is well documented and often discussed. We seldom hear about the paternal age effect on offspring health, although the link is now almost as solid as with maternal age. The causes behind this, however, are drastically different between males and females. CONTENT: In this review article, we will first examine documented physiological changes linked to paternal age effect. We will start with all morphological aspects of the testis that have been shown to be altered with aging. We will then move on to all the parameters of spermatogenesis that are linked with paternal age at conception. The biggest part of this review will focus on genetic changes associated with paternal age effects. Several studies that have established a strong link between paternal age at conception and the rate of de novo mutations will be reviewed. We will next discuss paternal age effects associated with telomere length and try to better understand the seemingly contradictory results. Finally, severe diseases that affect brain functions and normal development have been associated with older paternal age at conception. In this context, we will discuss the cases of autism spectrum disorder and schizophrenia, as well as several childhood cancers. SUMMARY: In many Western civilizations, the age at which parents have their first child has increased substantially in recent decades. It is important to summarize major health issues associated with an increased paternal age at conception to better model public health systems.